INASP journal publishing practices and standard course for the editors: an initiative to change the quality of academic journals - Roy, Bedanta; Sathian, Brijesh; Banerjee, Indrajit (Journal of Biomedical Sciences, 2018)
No abstract. JBS. 2016,3(4):33-34.